Screening A Trinucleotide Repeat Expansion: How precise PCR can be? - Ziske Maritska; Baharudin Baharudin; Ardy Santosa; Ching Leng Kee; Tan Yue Ming; Sultana MH Faradz (HM Publisher, 2019)
ABSTRACT Background. Trinucleotide Repeat Expansion (TRE) in human DNA could lead to various diseases. An expanded CAG repeat (>31 or 37 repeats, depends on the ethnicity) in Androgen Receptor gene is suggested to be associated with the occurrence of isolated hypospadias. In an effort to identify the exact numbers of repeats, sequencing has been the most favored method to be conducted despite its cost. Objective. This study wished to investigate the possibilities of using Polymerase Chain Reaction (PCR) method to screen expanded repeats in isolated hypospadias, as one of the TRE diseases. Materials and Methods. Numbers of CAG repeat in twelve hypospadias patients and one normal male was first predicted from the visualization of PCR products in 3% agarose gel electrophoreses with 20 bp ladder marker before it was finally sequenced. Results. Two samples gave the same exact result, while the rest showed a range of 1-11 bp differences. Statistically, there was a significant difference between the mean of CAG repeats from PCR method (M=26.1667, SD=6.71272) and the mean of CAG repeats from sequencing (M=23.75, SD=5.70685); t(11)= 4.570, p=0.001. Furthermore, the sensitivity of PCR was 100% and the specificity was 83.33%. Conclusion. It can be concluded that PCR method could be used as a screening method in identifying TRE with large numbers of repeats. However, PCR in TRE disease with small numbers of expanded repeats needs to be followed by sequencing in order to obtain the exact numbers of repeats. Keywords: Trinucleotide Repeat Expansion, Polymerase Chain Reaction, Sequencing, Isolated Hypospadias